Family Budget Data and Price-Elasticities of Demand - Leser, C. E. V. (Review of Economic Studies, 1941)
Journal Article Family Budget Data and Price-Elasticities of Demand Get access C. E. V. Leser C. E. V. Leser Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 9, Issue 1, November 1941, Pages 40–57, https://doi.org/10.2307/2967637 Published: 01 November 1941